2018
DOI: 10.1038/s41467-017-02624-8
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus-encoded US9 targets MAVS and STING signaling to evade type I interferon immune responses

Abstract: Human cytomegalovirus (HCMV) has evolved sophisticated immune evasion mechanisms that target both the innate and adaptive immune responses. However, how HCMV encoded proteins are involved in this immune escape is not clear. Here, we show that HCMV glycoprotein US9 inhibits the IFN-β response by targeting the mitochondrial antiviral-signaling protein (MAVS) and stimulator of interferon genes (STING)-mediated signaling pathways. US9 accumulation in mitochondria attenuates the mitochondrial membrane potential, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 59 publications
0
76
0
Order By: Relevance
“…The HCMV glycoprotein US9, encoded by US9, inhibits IFN-I by targeting mitochondrial antiviral-signaling protein (MAVS) and STING pathways (Choi et al, 2018). In this regard, Choi et al (2018) have proposed that US9 inhibits IRF3 nuclear accumulation by preventing STING dimerization. Moreover, the overexpression of US9 disrupts the mitochondrial membrane integrity and its membrane potential.…”
Section: The Ifn System and Hcmv: A Stormy Relationshipmentioning
confidence: 99%
“…The HCMV glycoprotein US9, encoded by US9, inhibits IFN-I by targeting mitochondrial antiviral-signaling protein (MAVS) and STING pathways (Choi et al, 2018). In this regard, Choi et al (2018) have proposed that US9 inhibits IRF3 nuclear accumulation by preventing STING dimerization. Moreover, the overexpression of US9 disrupts the mitochondrial membrane integrity and its membrane potential.…”
Section: The Ifn System and Hcmv: A Stormy Relationshipmentioning
confidence: 99%
“…Unlike BKPyV, HCV and some flaviviruses replicating in the cytoplasm appear to induce mitochondrial fragmentation and mitophagy in a PINK-Parkin-dependent fashion (Gou et al, 2017). Although structurally unrelated to agnoprotein, the 247aa-long cytomegalovirus 22 (CMV) US9 glycoprotein appears to suppress both MAVS and STING pathways, TBK-1 activation and IFN-β expression by disrupting the mitochondrial membrane potential in the late CMV replication phase (Choi et al, 2018;Mandic et al, 2009). Given the association of agnoprotein with LD, we were intrigued by the similarity to the antiviral host cell protein viperin, which is expressed following RNA-and DNA-virus infections (Gizzi et al, 2018;Hee and Cresswell, 2017).…”
Section: Innate Immune Sensors Have Been Characterized In Primary Hummentioning
confidence: 99%
“…Similarly, the E2 proteins of HPV16 inhibit the transcription of different ISGs by targeting STING (Sunthamala et al, 2014). Another study has shown that both human and mouse cytomegalovirus (CMV) induce a cGAS/STING-dependent type I IFN response or actively inhibit STING through its UL82 tegument protein or US9 glycoprotein (Choi et al, 2018; Fu et al, 2017; Lio et al, 2016). Several studies have shown that some retroviruses including HIV, murine leukemia virus, and simian immunodeficiency virus can induce a type I IFN response due to recognition of reverse-transcribed DNA by cGAS and subsequent production of cGAMP (Gao et al, 2013a; Lahaye et al, 2013; Rasaiyaah et al, 2013).…”
Section: Intracellular Recognition Of Dnamentioning
confidence: 99%